2020
DOI: 10.1093/gerona/glaa178
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Elevated suPAR, a New Biomarker of Inflammation, and Accelerated Aging

Abstract: Background To understand and measure the association between chronic inflammation, aging, and age-related diseases, broadly applicable standard biomarkers of systemic chronic inflammation are needed. We tested whether elevated blood levels of the emerging chronic inflammation marker soluble urokinase plasminogen activator receptor (suPAR) were associated with accelerated aging, lower functional capacity, and cognitive decline. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 50 publications
1
34
0
1
Order By: Relevance
“…A person's physical activity, such as the number of steps taken per day, is also considered a valuable indicator of biological age [14]. There are also studies assessing the "age of the brain" [15], the emergence of biomarkers of healthy aging [16], and biomarkers in blood plasma [17][18][19][20][21][22][23]. Biological age can also be calculated using telomerase activity and telomere length [24][25][26] or the degree of DNA or histone modifications [27,28].…”
Section: Approaches To Testing Biological and Psychological Agementioning
confidence: 99%
See 1 more Smart Citation
“…A person's physical activity, such as the number of steps taken per day, is also considered a valuable indicator of biological age [14]. There are also studies assessing the "age of the brain" [15], the emergence of biomarkers of healthy aging [16], and biomarkers in blood plasma [17][18][19][20][21][22][23]. Biological age can also be calculated using telomerase activity and telomere length [24][25][26] or the degree of DNA or histone modifications [27,28].…”
Section: Approaches To Testing Biological and Psychological Agementioning
confidence: 99%
“…A person’s physical activity, such as the number of steps taken per day, is also considered a valuable indicator of biological age [ 14 ]. There are also studies assessing the “age of the brain” [ 15 ], the emergence of biomarkers of healthy aging [ 16 ], and biomarkers in blood plasma [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, CRP and suPAR reflect different aspects of chronic inflammation despite both being used as inflammatory biomarkers 26 . In addition, unlike CRP, suPAR is a stable biomarker as circadian changes in plasma suPAR are minimal 27 29 , and suPAR measurements in individuals have been shown to be correlated across five and seven years 23 , 30 . We aimed to investigate whether suPAR plasma levels are under the genetic influence and if so, identify associated genetic variants that may facilitate our understanding of suPAR’s biology and its links to associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, suPAR has been investigated as a more stable biomarker of chronic inflammation, and elevated suPAR is closely linked to accelerated biological ageing, cognitive impairment, and development of inflammation-related diseases. [33][34][35] Of note, the higher suPAR level decreases the function of the urokinase plasminogen activator receptor system in endothelial cells and may lead to microcirculatory flow abnormalities. 36 In the present study, we observed a decrease in the De Backer score, the Consensus PPV, and the Consensus PPV (small) for every 1 ng/ml increase of preoperative suPAR.…”
Section: Discussionmentioning
confidence: 99%